Analisis Kinerja Keuangan dengan Rasio Liquiditas, Solvabilitas, Aktivitas dan Profitabilitas PT.XYZ - Ilham Ilham; Ismail Ismail; Muh. Alam Nasyrah Hanafi (Al-Buhuts, 2023)
This study aims to analyze the financial performance of PT. XYZ. performance is based on the ratio of liquidity, solvency, profitability, activity. The research method used is quantitative descriptive analysis. Data analysis techniques using financial ratio analysis. The results of this study indicate that: (1) in terms of the liquidity ratio, it indicates that the company is not liquid because it is below the industry average. (2) in terms of the Solvency ratio, it shows that the company is not solvable because the total assets owned by the company are unable to cover debts to outsiders and when measured using the ratio of debt to equity shows that the company is solvable because the capital owned by the company is able to cover the company's debts. (3) the activity ratio, measured using the debt turnover ratio shows that the company is not doing well, while the stock turnover of the company's condition shows good. (4) profitability ratios, the condition of the company is not good.